Enhanced selectivity to decalin in naphthalene hydrogenation under supercritical carbon dioxide - Hiyoshi, Norihito; Miura, R.; Rode, C. V.; Sato, O.; Shirai, M. (Chemistry Letters, 2005)
A charcoal-supported rhodium catalyst was highly active and selective to decalin for the hydrogenation of naphthalene at very low temperature (333 K) under supercritical carbon dioxide.